Cranfield situation awareness scale: Users Manual - Dennehy, K (Cranfield University, 1997)
Training to enhance situation awareness depends upon having satisfactory quantitative methods for measuring situation awareness. Until the development of the Cranfield-SAS, there was no direct subjective rating scale to measure the situation awareness of student (ab initio) civil pilots (see appendix 4 for an overview of the measurement guidelines for an overview of the measurement guidelines for scale development). The development of the scale was part requirement for a Ph.D. at Cranfield University. The benefits of such a technique is that a pilot’s progress in developing the skills necessary for situation awareness can be monitored. Instructors specifically can enhance the situation awareness of ab initio civil pilots in terms of: • Workload • Decision making • Design and Performance • Training The “Cranfield-Situation Awareness Scale (SAS)” is based on pilot actions and knowledge that the aviation community considered important to maintaining situation awareness. In general situation awareness refers to pilots knowledge and understanding of the situation in relation to the requirements of the flight task. The “Cranfield-SAS” is a subjective assessment technique and was developed as either an observer-rating (i.e. by instructors) or as a self-rating (i.e. by student pilots) during different predefined flight tasks (see appendix 3 for overview of observer/self-ratings). It is intended that this technique should ultimately be used during flight, flight simulation, or in the debriefing session. This users manual outlines how to use the Cranfield-SAS and has been distributed to instructors at flight schools (i.e. Great Britain and Canada) and to a major airline. The scale remains ownership of Cranfield University buy may be photo-copied (or requests for additional copies) and used freely by both instructors and students (for self-evaluation). As the scale is still under evaluation, we would request that the registration form (presented on a green page in the last page of the manual) be returned to: Dr. C.D. Deighton at the Applied Psychology Unit, Cranfield University. A short questionnaire will then be sent to you to obtain your comments on the structure and content of the scale.